Bosnia and Herzegovina : Fifth Review Under the Stand-By Arrangement and Request for Waivers of Applicability and Extension and Augmentation of the Arrangement. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
On January 31, 2014, the Executive Board of the IMF completed the fifth review of Bosnia and Herzegovina's economic performance under a program supported by a 24-month Stand-By Arrangement. The completion of the review enables the disbursement of an amount equivalent to SDR 42.275 million (about Euro 48 million), which will bring total disbursements under the arrangement to SDR 253.65 million (about Euro 287.9 million). All end-September 2013 performance criteria (PCs) and indicative targets were met. The Executive Board approved waivers of applicability of the now-controlling end-December 2013 PCs on the budget balances and accumulation of domestic arrears for the Institutions of Bosnia and Herzegovina and the entity central governments, for which data are not yet available and for which there is no evidence that they were not observed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet